The effect of using brainstorming strategy in improving decision-making skill in social studies (Asemi-experimental study of the fourth grade students of The Fourth graders in the first cycie of the basic learning inJableh City) - Jnad, Rawah; Safe, Alaa (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The study aimed at uncovering the effect of the use of brainstorming strategy in the improving the decision-making skills of the fourth grade students through their answers to a test that measures the decision-making skill in the social studies. It also aims to know the differences between the middle grades, the students who learned according to the brainstorming strategy and the pupils Who were taught according to the usual method. Accordingly, a semi-experimental approach was adopted. Abrainstorming strategy was designed for a unit of the fourth grade social studies book, and a test was designed to measure decision- (10) phrases, each of which included a problem to be decided on, and the educational program was applied to a sample of the fourth grade students in the first class of basic education (103) students and students in the school of martyr Yasser Kasu in the city of Jblah, The study shows that there is a statistically significant difference between the average scores of the students of the two groups (experimental and control) in the post-implementation and deferred to test the skill of decision making, and this difference is in the interest of the students of the experimental group. The study suggested that the brainstorming strategy should be applied in the teaching of the new curriculum, and studies should be carried out to reveal the impact of this strategy on the development of different thinking skills and in most subjects.